A mathematical model of CD8+ lymphocyte dynamics in HIV infection - Hraba, T; Dolezal, J (Folia biologica, 1995)
The previously developed mathematical model of CD4+ lymphocyte dynamics in HIV infection incorporated a homeostatic mechanism regulating production of both CD4+ and CD8+ lymphocytes. The model simulated the CD4+ lymphocyte dynamics well, but simulation of CD8+ lymphocyte values was not satisfactory, because simulated numbers of these cells increased even at later stages of infection, when no further increase was observed in infected individuals. Modifications of the model were attempted to obtain better simulation results assuming the influence of HIV infection on CD8+ lymphocyte maturation. Satisfactory results were obtained, if the influx of immature CD4+ and CD8+ lymphocytes was constrained by HIV infection. This modified version was then used for simulation of the anti-CD8 antibody administration effect in HIV-infected persons.
Keywords: HIV Infections; modely imunologické; HIV infekce; Mathematical Computing; lidé; CD8-Positive T-Lymphocytes; CD8-pozitivní T-lymfocyty; Models, Immunological; matematické výpočty počítačové; Humans